Pemanfaatan tepung rumput laut (Eucheuma cottonii) sebagai bahan baku pembuatan sabun transparan pelembab kulit - Ama Tasya'ul Hikmah; Hafiludin Hafiludin (AGROINTEK, 2025)
Seaweed (Seaweed) is one of the country's leading commodities in the fisheries sector which has the potential to be widely developed. Seaweed can be used as a cosmetic ingredient. One of the cosmetic products made from seaweed is soap. The carrageenan content in soap functions to moisturize the skin. This research used the Completely Randomized Design (CRD) method with the aim of determining the characterization of raw materials consisting of proximate analysis and characteristics of seaweed transparent solid soap including pH test, soap foam test, irritation test, sensory test and moisture test. Soap making used 4 different treatments with the addition of seaweed (F0: control), (F1: 1 g), (F2: 2 g) and (F3: 3 g). The results of the characterization of fresh, dry and flour Eucheuma cottonii seaweed raw materials were analyzed for water, ash, fat, fiber and protein content and had different nutritional content. The addition of Eucheuma cottonii seaweed flour had no significant effect (p.0.05) on the characteristics of seaweed soap which had a pH range of 10.29-10.45 and soap foam of 12.18-13.13 cm. Irritation tests were carried out on 12 panelists and 0 % found redness, itching and roughness. Sensory tests (transparency, aroma and impression after use) were carried out on 30 panelists and it was found that there were significant differences in soap transparency in each formula (p0.05) and no significant differences in aroma and impression after using soap (p0.05). . The results of the moisture test using a skin analyzer showed that the panelists' skin moisture before using transparent soap ranged from 38.81-39.36 % and after using transparent soap it ranged from 45.63-47.09 %. The transparent solid soap formulation provided a significant skin moisturizing effect (p0.05). The highest humidity is in F3, namely by adding 3 g of seaweed flour (Eucheuma cottonii).